(untitled) (World Bulletin of Public Health, 2024)
In the 21st century, tumors are becoming one of the main problems in the field of medicine, and if you look closely at the statistics, from year to year the incidence of malignant neoplasms (MNT) is increasing compared to benign ones. The issues of diagnosis and treatment of cancer in the early stages remain relevant today throughout the world. In addition, there is no fullfledged algorithm that answers all the questions regarding the management of patients with such serious complications as acute obstructive intestinal obstruction, intestinal perforation due to tumor disintegration, and bleeding from the tumor.